Pair-instability supernovae in the local universe - Whalen, Daniel J.; Smidt, Joseph; Heger, Alexander; Hirschi, Raphael; Yusof, Norhasliza; Even, Wesley; Fryer, Chris L.; Stiavelli, Massimo; Chen, Ke-Jung; Joggerst, Candace C. (The astrophysical journal, 2014)
The discovery of 150-300 M ☉ stars in the Local Group and pair-instability supernova candidates at low redshifts has excited interest in this exotic explosion mechanism. Realistic light curves for pair-instability supernovae at near-solar metallicities are key to identifying and properly interpreting these events as more are found. We have modeled pair-instability supernovae of 150-500 M ☉ Z ∼ 0.1-0.4 Z ☉ stars. These stars lose up to 80% of their mass to strong line-driven winds and explode as bare He cores. We find that their light curves and spectra are quite different from those of Population III pair-instability explosions, which therefore cannot be used as templates for low-redshift events. Although non-zero metallicity pair-instability supernovae are generally dimmer than their Population III counterparts, in some cases they will be bright enough to be detected at the earliest epochs at which they can occur, the formation of the first galaxies at z ∼ 10-15. Others can masquerade as dim, short duration supernovae that are only visible in the local universe and that under the right conditions could be hidden in a wide variety of supernova classes. We also report for the first time that some pair-instability explosions can create black holes with masses of ∼100 M ☉.
Gesehen am 01.07.2020